Discrete element method simulations of Mars Exploration Rover wheel performance. (December 2015) - Johnson, Jerome B.; Kulchitsky, Anton V.; Duvoy, Paul; Iagnemma, Karl; Senatore, Carmine; Arvidson, Raymond E.; Moore, Jeffery
Highlights: Discrete element simulations of a Mars Exploration Rover wheel were conducted. At wheel slips ⩾30% simulations differed from drawbar pull data by 2–16%. At wheel slips ⩾30% simulations differed from sinkage data by 0.45–50%. Strength from soil particle interlocking controls wheel performance at low slip. Interparticle friction and wheel contact area control high slip wheel performance. Abstract: Mars Exploration Rovers (MERs) experienced mobility problems during traverses. Three-dimensional discrete element method (DEM) simulations of MER wheel mobility tests for wheel slips of i  = 0, 0.1, 0.3, 0.5, 0.7, 0.9, and 0.99 were done to examine high wheel slip mobility to improve the ARTEMIS MER traverse planning tool. Simulations of wheel drawbar pull and sinkage MIT data for i  ⩽ 0.5 were used to determine DEM particle packing density (0.62) and contact friction (0.8) to represent the simulant used in mobility tests. The DEM simulations are in good agreement with MIT data for i  = 0.5 and 0.7, with reasonable but less agreement at lower wheel slip. Three mobility stages include low slip ( i  < 0.3) controlled by soil strength, intermediate slip ( i  ∼ 0.3–0.6) controlled by residual soil strength, and high slip ( i  > 0.6) controlled by residual soil strength and wheel sinkage depth. Equilibrium sinkage occurred for i  < 0.9, but continuously increased for i  = 0.99. Improved DEM simulation accuracy of low-slip mobility can be achieved using polyhedral particles, rather than tri-sphere particles, to represent soil. The DEM simulations of MER wheel mobility can improve ARTEMIS accuracy.